Co-exposure to toxic metals and phthalates in pregnant women and their children’s mental health problems aged four years — Taiwan Maternal and Infant Cohort Study (TMICS) - Tsung-Lin Tsai; Chia-Jung Hsieh; Ming-Tsang Wu; Mei-Lien Chen; Po-Hsiu Kuo; Shu-Li Wang (Environment International, 2023)
Background: Childhood and adolescent mental health problems may increase the global burden of disease. Neurotoxic metals are associated with inflammation and cytotoxicity in the brain. In addition, prenatal phthalate ester (PAE) exposure is associated with cognitive function deficits. However, the effect of co-exposure to toxic metals, PAEs, and their association with child behavior is less well studied. Hence, we aimed to investigate prenatal co-exposure to the metals and PAEs and the consequent behavioral outcomes in early childhood. Methods: We followed pregnant women and their newborns from the Taiwan Maternal and Infant Cohort Study between 2015 and 2017, with a focus on women from the central, southern, and eastern areas of Taiwan. We quantified maternal urinary concentrations of metals and metabolites of PAEs as surrogates of prenatal exposure. We recorded the Child Behavior Checklist scores according to caregiver reports at 4 years of age, and identified Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5)-oriented problems. Results: Ultimately, 408 children were included in the statistical analysis. Maternal urinary copper levels were significantly associated with depressive problems (odds ratio [OR] = 2.13) in children. Maternal urinary concentrations of mono-n-butyl phthalate (MnBP) and mono-isobutyl phthalate (MiBP) were also significantly associated with depressive symptoms (odds ratio [OR] = 1.51 and 1.53, respectively). Further analysis considering prenatal co-exposure to metals and PAEs showed that co-exposure to these materials was significantly associated with autism spectrum problems (OR = 3.11). Conclusions: We observed that prenatal single exposure or co-exposure to metals and PAEs may play a role in some DSM-5-oriented problems in children at 4 years of age. Reduction of exposure to toxic metals and PAEs in pregnancy is suggested to prevent increased mental health problems in children.